The outcomes of delayed treatment for open fracture diaphyseal forearm - Rahim, Mohamad Afif Ab (2016)
Introduction Open fractures considered as orthopaedic emergency and need prompt wound debridement to prevent infection. However due to unavoidable circumstances debridement cannot be performed perform within 12 hours. Furthermore, some times wound debridement was delayed up to more than 48 hours. The purpose of this study to review on the outcome of diaphyseal forearm open fracture when wound debridement was performed according different time classification Methods A five-year secondary data review on the outcome of diaphyseal forearm open fractures patients admitted to our centre between 2008 and 2013. Patients with grade IIIc open fractures were excluded. Demographic data, time of debridement, present of infection and type of union were recorded. Results We had 26 cases of open fracture diaphyseal forearm with 10 cases Grade I, seven cases Grade II, 8 cases Grade IIIa and 1 case Grade IIIb. There was one non union with no soft tissue infection or osteomyelitis among patients with wound debridement done before 12 hours of injury. One soft tissue infection without osteomyelitis cases and one non union case among patients with wound debridement done with 13-24 hours of injury. There was one soft tissue infection with osteomyelitis case and one non union case among patients who had debridement after 24 hours of injury. Conclusion There was a proportionate higher risk of infection if wound debridement was delayed more than 12 hours. Osteomyelitis was proportionately higher if wound debridement was done after 24 hours of injury. Non union was proportionately similar if wound debridement was done before 12 hours, within 13-24 or after 24 hours of injury.